COVID-19 restrictions: impact on lifestyle and social behaviour among adults of 18-40 years in Kurnool town - Deepthi, Kommula; Pasha, M. A. M.; Fatima, Afsar (International Journal Of Community Medicine And Public Health, 2022)
Background: With the unprecedent spread of COVID-19, lockdown had been implemented in the country as a preventive strategy to reduce transmission. This pandemic born lockdown has affected the lifestyle and social behaviours of individuals. Methods: A web based cross-sectional study was conducted among adults of 18-40 years in Kurnool town through snow ball sampling method. Data was collected using pre-tested, pre-designed, semi-structured questionnaire through google forms and the data was analysed using SPSS version 22. Results: The 53.8% of the participants were not doing any physical exercises. Only 47.8% had changed to a healthy diet during lockdown. The 38.3% perceived an increase in their weight during lockdown. The 12.6% had decreased or tried to cut-down alcohol consumption. Conclusions: Overall there was a negative impact on the lifestyle behaviour in our study. There is a need for health education and lifestyle behaviour programmes.